Investigating the Psychological Aspects of Cyber Socialization Among Modern Students - Shitova, Nina V. (2020)
The article presents the psychological analysis of cyber socialization process among modern students. The main sources of empirical research are the results of student subjective perception of activity diagnostics in the information and communication space of Internet and the analysis of data on the symptoms of information stress due to the active use of cyber-resources by students.